Changing trends in fetomaternal outcome in COVID-19 in pregnancy - Parikh, Purvi M.; Vyas, Rupa C.; Bhatiya, Rekha K.; Shah, Sapana R.; Chudasama, Tanmay J. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: This study is to provide an overview of the clinical course and outcome of COVID in pregnancy in both first wave and second wave, to study about different parameters affected significantly in both waves. Methods: This is a retrospective comparative study that was conducted by dividing the patients into group 1 and group 2. Group 1 was treated in 2020 (wave 1) whereas group 2 in 2021 (wave 2). A laboratory confirmed positive cases of COVID-19 infection in pregnant women were included. All the patients were further categorized into mild, moderate and severe subgroups according to the ICMR criteria. Results: The study of the first (2020) and second (2021) wave of COVID-19. In group 1 and group 2, there were a total of 359 cases and 145 cases respectively. In group 1, there were 54/359 (15.04%) moderate cases and in group 2 there were 17/145 (11.72%) moderate cases. While there were 101/359 (28.13%) and 106/145 (73.10%) severe cases in group 1 and group 2 respectively. Most of severe cases of second group associated with breathlessness, tachypnoea and fall in oxygen saturation level ended with mechanical ventilation by O2 mask (7.54%), NRBM (8.49%), HFNC (14.15%), BIPAP (12.26%), invasive ventilation (22.64%). Conclusions: The results of study show that hospitalized patients in the second wave were younger, required hospitalization, and had higher mortality rates.